The potential of biographite formation from sago waste at different pyrolysis temperatures - Nurjehan Faratul Sabrina, Kamaruddin; Siti Kudnie, Sahari; Ibrahim, Yakub; Marini, Sawawi; Mohamad Rusop, Mahmood; Ramzan, Mat Ayub; Zainab, Ngaini; Yanuar Zulardiansyah, Arief; Lilik, Hasanah; Rafeah, Wahi (PENERBIT UniMAP, 2026)
This study explores the potential of sago palm trunk as a precursor for synthesizing biographite for fuel cell applications. Pyrolysis was conducted at 500℃, 600℃, and 700℃, both in the presence and absence of iron (III) nitrate nonahydrate as a catalyst. The primary objective is to form biographite through pyrolysis at low heating temperatures. All samples were characterized by using scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and a 3D digital microscope. Only the catalyst-treated samples were further analysed using X-ray diffraction (XRD) and Raman spectroscopy. To evaluate fuel cell performance, microbial fuel cells (MFCs) were constructed using the samples as bipolar plates. Results suggest that amorphous graphite can form at 500°C without a catalyst, whereas catalytic pyrolysis leads to the formation of nanocrystalline graphite. Among all tested samples, the catalyst-assisted pyrolysis at 600°C demonstrated the best fuel cell performance. These findings confirm the potential of the sago palm trunk for biographite synthesis. However, further optimization of the pyrolysis process beyond temperature control is needed to obtain crystalline graphite with enhanced electrical properties.